Rare earth metal as a dopant element: Cerium ion as an articulator in hexavalent chromium removal by magnetic iron oxides - Chagas, Pricila Maria Batista; Lima, Maísa M.M.; Caetano, Aline Aparecida; Carvalho, Lucas Bragança [UNESP]; Piva, Nayra Maria de Abreu; Luiz, Maria Eduarda Resende; Guimarães, Iara do Rosário (Elsevier, 2023)
This study highlights introducing the rare earth metal cerium (Ce(IV)) into the structure of magnetite (Fe3O4) to achieve enhanced adsorptive properties for the removal of chromium (Cr(VI)) from an aqueous medium. Different ratios of Ce(IV) were introduced into the iron oxide matrix, termed FeCe-5, FeCe-10, and FeCe-20. Their numerical values correspond to the nominal content of the dopant element added to the synthesis medium. The solid materials were characterized for morphology and chemical structure, and N2 physical adsorption/desorption measurements were performed. The solid materials doped with Ce(IV) have a high surface area compared to Fe3O4, and the solid material with the highest content of the dopant ion (Ce(IV)) has a 4-fold greater surface area. This increase in the dopant content in the iron oxide structure leads to a total chromium removal of 93.3%. Isotherms studies on the solid materials show that chromium adsorption follows the Langmuir model. The adsorption capacity to Fe3O4 is 12.59 mg/g and FeCe-10 is 22.49 mg/g at 35 °C. By fitting the kinetic and isothermal models, it is found that for the Fe3O4 and FeCe-10 materials Cr(VI) removal occurs in very different ways, attributed to the different surface areas and compositions of the oxide, with the formation of the goethite (α-FeOOH) phase. The FeCe-10 reuse process was performed and the removal capacity the Cr(VI) is reduced after the first cycle. This result is attributed to a strong and irreversible adsorption of Cr(VI) on the FeCe-10.
Keywords: Adsorption; Bimetallic oxides; Cr(VI); Fe–Ce interaction; Oxygen vacancies; Rare earths